Studies on non-typeability and molecular identification of the pneumococcus - Tavares, Débora A. (2016)
Pneumococcus(is(a(major(human(pathogen.(Its(main(virulence(factor(is(the(capsule,( which( is( of( polysaccharide( nature.( The( detection( of( the( capsule( using( specific( antisera( is( used( to( identify( pneumococcus.( Also,( differences( in( structural( and( antigenic(properties(of(the(polysaccharides(composing(the(capsule(have(been(used( to(classify(pneumococcus(into(serotypes.(